PENDEKATAN PEMECAHAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI TRIGONOMETRI - Hayati, Rahmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
This study is entitled Problem Solving Approach to improve student learning outcomes in Trigonometry Materials. The purpose of this study is to describe learning that can improve student achievement with the Problem Solving Approach in Trigonometry Materials in Class X SMA Negeri 1 Bireuen. This study uses a qualitative approach to the type of Classroom Action Research (CAR). As for the subjects of the study were all grade X students of SMA Negeri 1 Bireuen and 5 students were taken as interview subjects with high, medium, and low ability criteria. Research data collected in the form of tests, interview observations and field notes. Student responses about problem solving approaches were also very good. It was proven that they enjoyed learning with the problem solving approach. This research was carried out in one action with II cycle. In the first cycle, the results of the study showed that the observations of the researchers 'activities reached 87.50% and the results of observations of the students' activities reached 81.67%. While the success of the final test of the first cycle I action reached 78.13%. Thus according to the established criteria said to be unsuccessful, for that the researcher entered the second cycle and corrected the existing weaknesses in cycle I. In the second cycle, the results of the study showed that the observations of the researchers 'activities reached 91.67% and the results of observations of the students' activities reached 89.17%. While the success of the final test cycle II action reached 87.10%. Based on the results of the final test I cycle II action that learning has reached the specified criteria that is 85% of students got a score ≥ 65 so that this study was said to be successful. Student responses about problem solving approaches were also very good. It was proven that they enjoyed learning with a problem solving approach.